DESIGNING A HEALTHY MENU PROJECT FOR INDONESIAN JUNIOR HIGH SCHOOL STUDENTS - Ratu Ilma Indra Putri; Zulkardi Zulkardi; Ninik Purwaning Setyorini; Agyta Meitrilova; Ranni Permatasari; Sulafah Ansya Saskiyah; Duano Sapta Nusantara (Journal on Mathematics Education, 2021)
Project-based learning (PjBL) is an appropriate learning model that can shape students’ scientific, social and higher-order thinking. Implementing PjBL in education gives students the freedom to plan their own learning activities, conduct projects collaboratively and produce products. In a healthy menu project, PjBL can help students calculate their excess weight. The purpose of this study was thus to design a healthy menu that assists Indonesian junior high school students solve numeracy problems using obesity context. The method followed a design research type validation studies using observation and document reviews as data collection techniques. This study produced a learning trajectory that can help grade VII students solve arithmetic operations using obesity context through two activities. In the first, the students were asked to record their respective heights and weights, then use them to determine their body mass index (BMI) and body mass ratio (BMR). Then, the students confirmed their necessary daily caloric intake, and categorized their BMI and BMR results as underweight, normal, overweight or obese. In the second activity, the students developed healthy menus per their respective tastes based on their weight categories from the first activity. The study concluded with the students successfully producing healthy menus that they designed according to their calculated required daily caloric intake.